Evaluation of Mean Performance and Stability of Lentil Genotypes According to Combination of Additive Main Effects and Multiplicative Interaction, and Best Linear Unbiased Prediction Methods - Payam Pezeshkpour; Bita Naseri; Reza Amiri; Amir Mirzaei; Seyedeh Soudabeh Shobeiri; Iraj Karami (Legume Science)
ABSTRACT This research (2020–2022) aimed to evaluate the interaction of genotype × environment with seed yield and stability of performance for 19 lentil genotypes and cultivars using additive main effects and multiplicative interaction (AMMI) and best linear unbiased prediction (BLUP) in a rainfed, semi‐temperate region. Results of the likelihood ratio test (LRT) showed significant effects of genotype and genotype × environment interaction on seed yield, suggesting the best BLUP for datasets. Based on the AMMI stability value (ASV), Genotypes 8, 2, 12, 10, and 5 were stable in performance. According to two principal components of AMMI, Genotypes 10, 11, and 2 were stable in performance. Mosaic graph indicated that genotype and genotype × environment interaction explained 15.45% and 84.55% of total variance, respectively. The weighted average of mean performance (WAASBY) index according to BLUP showed high‐yielding and performance stability of Genotypes 6, 12, and 15. Therefore, the WAASBY index was determined to be the best index to evawluate stable lentil genotypes across different environments.